ONLINE FOOD ORDER APPLICATION USING DJANGO (International Journal of Food and Nutritional Sciences, 2022)
With the growing popularity of food delivery,conventional phone order has becomeinconvenient for both customers and food deliverystores. People are concerned about how to makefood delivery more timely and convenient.